Interactive Ilokano Mother Tongue-Based Courseware for Grade 1 Mathematics: Development and Usability - Guidang, Excel Philip B.; Alagao, Caren Q.; Alvarez, Marygrace B.; Carreon, Jhayzel Blanca T.; Alcalde, Madelyn A.; Quintinita, Lezlee L. (JPAIR Institutional Research, 2015)
Tablets, Smartphones, and Phablet, attract so much the attention of pupils because of the things that they can do with these gadgets. The study developed a mother tongue-based courseware for Grade 1 Mathematics and undergone usability testing at the Abra State Institute of Sciences and Technology, Lagangilang, Abra, Philippines. It employed the descriptive and applied methods of research. Documentary analysis was used to identify the topics covered in Grade 1 mathematics. The ADDIE model was used to develop the courseware. Finally, a questionnaire that was designed to evaluate multimedia systems was adopted. The study found out that the topics covered in Grade 1 Mathematics of the ASIST-LS were divided into Quarters 1 and 2, and Quarters 3 and 4. Quarters 1 and 2 consist of Maysa Inggana Sangapulo, Sangapulo ket Maysa Inggana Duapulo, Duapulo ket Maysa Ingana Limapulo, Limapulo Inggana Sangagasut, Skip Counting by Twos, and Skip Counting by Tens. Quarters 3 and 4 consist of Addition, Shape, Using the Calendar, and Comparison of Things. The developed courseware provides pupils ability to repeat the topics and activities that lead them to master the lesson at their own pace. The usability survey result revealed that courseware was usable.